2020
DOI: 10.1111/pim.12711
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis vesicular fluid induces the expression of immune checkpoint proteins in vitro

Abstract: Aims: Alveolar echinococcosis is a severe chronic helminthic infection that mimics a tumour-like disease. This study aimed at investigating in vitro interactions between Echinococcus multilocularis vesicular fluid (VF) and different immune checkpoints (PD-1/PD-L1, CTLA-4, LAG-3 and TIM-3). Methods and Results: Peripheral blood mononuclear cells (PBMC) from healthy blood donors were isolated by Ficoll. Natural killer (NK) cells were selected. Each type of cell was stimulated individually with E. multilocularis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…( 28,29 ) Furthermore, Em ‐VF induces the expression of inhibitory receptors (including PD‐1, LAG‐3, and TIM‐3) on the surface of NK cells and inhibits NK cell activation and proliferation ex vivo . ( 12 ) Hence, these results suggest that Fgl2, IL‐27, or E. multilocularis –derived antigens might contribute to up‐regulated expression of TIGIT in NK cells during echinococcosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…( 28,29 ) Furthermore, Em ‐VF induces the expression of inhibitory receptors (including PD‐1, LAG‐3, and TIM‐3) on the surface of NK cells and inhibits NK cell activation and proliferation ex vivo . ( 12 ) Hence, these results suggest that Fgl2, IL‐27, or E. multilocularis –derived antigens might contribute to up‐regulated expression of TIGIT in NK cells during echinococcosis.…”
Section: Discussionmentioning
confidence: 78%
“…( 15 ) Available data have shown that E. multilocularis and its antigen inhibit the function of NK cells by up‐regulating the expression of inhibitory receptors, including NKG2A, PD‐1, and LAG‐3. ( 12 ) We found that NK cells from the blood and CLT of AE patients expressed a higher level of inhibitory receptor TIGIT, which was reported to inhibit the activation of NK cells in tumors or chronic infection. ( 18,23 ) Our study showed that TIGIT + NK cells in the peripheral blood or CLT of AE patients were functionally exhausted with lower expression of granzyme B, perforin, IFN‐γ, and TNF‐α.…”
Section: Discussionmentioning
confidence: 95%
“…Other supporting research was found to be in agreement with the above inference. Confirmation of this hypothesis was brought about by a control in the infection utilising immunotherapy which acted on PD-L1 pathway blockage [72,73].…”
Section: Immune Checkpoint Inhibitormentioning
confidence: 92%
“…Last, there are many diseases in which immune checkpoints seem to be highly important, e.g., parasitic infections such as helminthiasis, toxoplasmosis, and malaria ( 8 , 148 , 149 ), yet further research is necessary to develop effective therapeutic approaches.…”
Section: Concluding Remarks and New Directionsmentioning
confidence: 99%